Tahap Amalan dan Pengintegrasian ICT dalam Proses Pengajaran dan Pembelajaran Sains (Sains Humanika, 2014)
This article aims to report research results regarding Science teacher’s level of awareness and practice towards importance of ICT integration in the process of teaching and learning. The study was carried out using descriptive design. Instrument used comprised Likert scale questionnaire. A total of 66 teachers in 7 schools were chosen based on a random sampling basis. Data were analysed using descriptive analysis which included frequency, percentage and mean.Results from the study showed most teachers had a high level of awareness towards the importance of ICT integration in the process of teaching and learning Science. However, teacher’s practice of ICT application in the process of teaching and learning Science was average. This result set off an understanding regarding the continuous need to encourage ICT practice among teachers to increase the effectiveness of teaching and learning Science.
Keywords: ICT integration; awareness and practice; teaching and learning; science education; teacher